Perancangan Sistem Informasi Pengingat Kontrol Aset Barang Berbasis Android Pada PT. ISUZU - Christian Boy Aritonang; Andrew Fernando Pakpahan; Yulianus Palopak (TeIKa, 2019)
In this modern days, humans really need technology in their daily life, like PT.ISUZU. where this business need one thing that can help the workers in remembering to control the items. One thing that can help the workers are device that can give reminder to them about things that need to be controlled. In this case, the system is counted to help the workers in controlling the items well. The method that are used in this research is SDLC method (System Development Life Cycle) which was started from needs analysis, design system, coding and testing. The purpose of this research is to help the workers in controlling the items well through application system that will be built. As a result, the Android-based information system reminder control can help the workers in remembering to control items through notifications that were given by the device to the workers.